Executioner caspase-3, -6, and -7 perform distinct, non-redundant roles during the demolition phase of apoptosis. - MARTIN, SEAMUS (My University, 2001)
Members of the caspase family of cysteine proteases play central roles in coordinating the stereotypical events that occur during apoptosis. Because the major executioner caspases, caspase-3 and caspase-7, exhibit almost indistinguishable activity toward certain synthetic peptide substrates, this has led to the widespread view that these proteases occupy functionally redundant roles within the cell death machinery. However, the distinct phenotypes of mice deficient in either of these caspases, as well as mice deficient in both, is at odds with this view. These distinct phenotypes could be related to differences in the relative expression levels of caspase-3 and caspase-7 in vivo, or due to more fundamental differences between these proteases in terms of their ability to cleave natural substrates. Here we show that caspase-3 and caspase-7 exhibit differential activity toward multiple substrate proteins, including Bid, XIAP, gelsolin, caspase-6, and cochaperone p23. Caspase-3 was found to be generally more promiscuous than caspase-7 and appears to be the major executioner caspase during the demolition phase of apoptosis. Our observations provide a molecular basis for the different phenotypes seen in mice lacking either caspase and indicate that these proteases occupy nonredundant roles within the cell death machinery.
PUBLISHED
Keywords: Biochemistry; cell death machinery